2014
DOI: 10.1007/s11224-014-0539-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooperativity in lithium bonding on the strength of hydrogen bonding: (LiCN) n ···HX (n = 1–5, X = F, Cl) complexes as a working model

Abstract: Quantum chemical calculations are performed to analyze effect of cooperativity in lithium bonding on the strength of hydrogen bonding. Molecular geometries and interaction energies of the complexes are investigated using the MP2 method employing 6-311 ??G** basis set. Our results reveal that strength of hydrogen bonding is enhanced due to cooperativity between lithium bonded complexes. Cooperative effects are found when lithium and hydrogen bonds coexist in the title complexes. These effects are studied in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The mentioned contractions with complex size in the r Li···N and r Cl···N bonds of (LiCN) n ··· ClYF 3 complexes can be referred to cooperative effects in these systems. Unlike the contraction of hydrogen bonding in (LiCN) n ···HF(HCl) complexes [50], the shrinkage in halogen bonding distances in (LiCN) n ···ClYF 3 is less dependent to complex size.…”
Section: Results and Discussion Geometriesmentioning
confidence: 93%
See 1 more Smart Citation
“…The mentioned contractions with complex size in the r Li···N and r Cl···N bonds of (LiCN) n ··· ClYF 3 complexes can be referred to cooperative effects in these systems. Unlike the contraction of hydrogen bonding in (LiCN) n ···HF(HCl) complexes [50], the shrinkage in halogen bonding distances in (LiCN) n ···ClYF 3 is less dependent to complex size.…”
Section: Results and Discussion Geometriesmentioning
confidence: 93%
“…So far, more attention has been paid to the cooperativity between Li-bonds [44][45][46][47][48][49]. Very recently, we have demonstrated that strength of hydrogen bonding is enhanced due to cooperativity between lithium bonded complexes in (LiCN) n ···HX (n=1-5, X=F, Cl) [50].…”
Section: Introductionmentioning
confidence: 99%